(untitled) (Journal of actual problems of jurisprudence, 2018)
This article discusses the most important branch of the criminal procedural functions of prosecution and defense functions of adjudication by the court. As a result of the study conclude that the principle of equality of the parties, should be the basis for the resolution of cases and provide more opportunities for the procedural parties for proof. Key words: The court, the defense, the prosecution, the competitiveness, the prosecution lawyer.